Numerical Modeling of Estuarine Circulation in the Geum River Estuary, Korea. (2016) - Cho, Jaegab; Song, Yongsik; Kim, Tae In
Abstract: The natural estuarine environment in Geum River Estuary (GRE) has been altered by the GRE dam since 1994. A circulation model of GRE as a basis of real-time prediction system for environmental management is established. Through the model calibration and validation, it is found that the model reproduces physical variables in a reasonable manner. In normal season, the vertical salinity gradient and the stability of water mass alternate periodically according to the tidal range. High freshwater runoff in summer changes greatly the salinity structure and the unstable state of water mass is maintained in front of the dam irrespective of the tidal range. Two-layer circulation with less saline surface water flowing offshore and more saline bottom water flowing upstream, is found all the year round. Especially in summer, the gravitational circulation is more conspicuous due to enlarged salinity gradient. The circulation pattern of the estuary is largely governed by the seasonal variation of freshwater discharge from the dam.